Risk factors associated with ectopic pregnancy in our sociodemographic setup - Gandotra, Nikita; Zargar, Shazia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ectopic pregnancy (EP) is assuming greater importance because of its increasing incidence and its impact on woman’s fertility. Aim: To assess the frequency and to determine an association between the studied risk factors and ectopic pregnancy. Methods: A retrospective study was conducted for the role of several risk factors in the occurrence of EP in department of obstetrics and Gynaecology, SMGS Hospital. A total of 110 cases and 110 controls were compared for socio demographic characteristics, cigarette smoking, obstetrical and gynaecological history, PID, past exposure to Chlamydia, surgical histories, the presence of assisted conception and contraceptive usage. Results: The main risk factors for ectopic pregnancy were history of tuberculosis (TB) (odds ratio (OR)=12.11), history of infertility (p=0.001), abortions (p=0.01) and a history of prior ectopic pregnancy (OR=8.549). Other risk factors found to be associated with an increased risk for ectopic pregnancy were Pelvic inflammatory disease (PID)/Chlamydia infection (OR=5.63), endometriosis (5.40), induced conception cycle (OR=3.063), intrauterine device usage (OR=3.55), prior caesarean section (OR=2.83) and appendectomy (OR=2.25). On the contrary, barrier methods (OR=0.28) and oral contraceptive use (OR=0.28) were protective from ectopic pregnancy. Conclusion: Pelvic infection particularly TB was found to be a major etiological factor for EP in our setup. Furthermore, other factors found to be associated with ectopic pregnancy, such as prior ectopic pregnancy and infertility history may be the result of a previous pelvic infection that caused tubal sequele. Thus, these factors are potential targets for intervention and modification. Further, patients with previous abortions, pelvic surgeries, induced conception cycle and intrauterine contraceptive device (IUCD) users should be counselled about the possible risk when they conceive.